Pseudomonas aeruginosa Biofilm: A New PqsR Inverse Agonist Potentiates Tobramycin Efficacy to Eradicate Pseudomonas aeruginosa Biofilms (Adv. Sci. 12/2021). Issue 12 (24th June 2021) - Schütz, Christian; Ho, Duy‐Khiet; Hamed, Mostafa Mohamed; Abdelsamie, Ahmed Saad; Röhrig, Teresa; Herr, Christian; Kany, Andreas Martin; Rox, Katharina; Schmelz, Stefan; Siebenbürger, Lorenz; Wirth, Marius; Börger, Carsten; et al.
Abstract : In article number 2004369, Martin Empting and colleagues describe a new generation of dual‐loaded nanoparticles enabling efficient eradication of Pseudomonas aeruginosa biofilms. The squalene‐based nanocarrier facilitates co‐delivery of a novel pathogenspecific Quorum Sensing Inhibitor (QSI) together with the standard‐of‐care antibiotic tobramycin. The QSI itself shows high anti‐virulence efficacy, favorable DMPK and no overt safety pharmacology. When applied as the nanoparticle formulation the QSI potentiates biofilm eradication capabilities of tobramycin by at least 32‐fold.